2022
DOI: 10.3390/jcm11154370
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Renal Allograft Stiffness and Viscosity Using 2D SWE PLUS and Vi PLUS Measures—A Pilot Study

Abstract: Elastography is a useful noninvasive tool for the assessment of renal transplant recipients. 2D-shear wave elastography (SWE) PLUS and viscosity plane-wave ultrasound (Vi PLUS) have emerged as novel techniques that promise to offer improved renal stiffness and viscosity measures due to improved processing algorithms. Methods: We performed a cross-sectional study of 50 kidney transplanted patients (16 women, 34 men; mean age of 47.5 ± 12.5; mean estimated glomerular filtration rate (eGFR) estimated by Chronic K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The mean 2D-SWE PLUS and Vi PLUS measurements decreased with age but were unaffected by the participant’s sex. In addition, we also published a study on kidney transplant recipients evaluated using the same elastography measurements in which we obtained a cut-off value of 27.3 kPa for estimating an eGFR of under 60 mL/min/1.73 m 2 , and this also indicated that, when the disease advances, renal stiffness declines [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean 2D-SWE PLUS and Vi PLUS measurements decreased with age but were unaffected by the participant’s sex. In addition, we also published a study on kidney transplant recipients evaluated using the same elastography measurements in which we obtained a cut-off value of 27.3 kPa for estimating an eGFR of under 60 mL/min/1.73 m 2 , and this also indicated that, when the disease advances, renal stiffness declines [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead of rapid deformation, slow deformation causes tissues to migrate, and necro-inflammation-related alterations are thought to affect how shear waves propagate (viscosity) [ 18 ]. Supersonic Imagine created the original 2D-SWE method, and numerous studies and meta-analyses have supported its usefulness in fibrosis assessment [ 19 , 20 , 21 , 22 ], but, currently, there are only a few research articles employing the new 2D-SWE PLUS and Vi PLUS technologies [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of available research has focused on characterizing the viscoelastic properties of the in vivo kidney using the KV model fitting approach [ 43 ], [ 44 ], [ 45 ], [ 46 ], [ 47 ], [ 48 ], [ 49 ]. The Aixplorer Mach 30 ultrasound scanner from Hologic was utilized to estimate shear elasticity and viscosity within the ranges of 5–10 kPa and 2–3 Pa · s, respectively [ 43 ], [ 44 ], [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of available research has focused on characterizing the viscoelastic properties of the in vivo kidney using the KV model fitting approach [ 43 ], [ 44 ], [ 45 ], [ 46 ], [ 47 ], [ 48 ], [ 49 ]. The Aixplorer Mach 30 ultrasound scanner from Hologic was utilized to estimate shear elasticity and viscosity within the ranges of 5–10 kPa and 2–3 Pa · s, respectively [ 43 ], [ 44 ], [ 45 ]. Some limited data also exist, employing the shear dispersion ultrasound vibrometry (SDUV) method, which involves generating shear waves at frequencies that are multiples of 100 Hz [ 46 ], [ 47 ], [ 48 ], [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In peripheral muscle, both 2D-SWE and viscosity parameters presented statistically significant differences between pre-and post-contraction settings [ 30 ]. Together with shear-wave elastography, tissue viscosity was also found to be useful in monitoring renal allograft in transplanted patients and detecting chronic injury [ 31 ]. In patients with chronic liver disease, spleen stiffness had better diagnostic quality than spleen viscosity, although they both correlated with the presence of liver disease [ 32 ].…”
Section: Discussionmentioning
confidence: 99%